The PD-1 Pathway Regulates Development and Function of Memory CD8+ T Cells following Respiratory Viral Infection - Pauken, Kristen E.; Godec, Jernej; Odorizzi, Pamela M.; Brown, Keturah E.; Yates, Kathleen B.; Ngiow, Shin Foong; Burke, Kelly P.; Maleri, Seth; Grande, Shannon M.; Francisco, Loise M.; Ali, Mohammed-Alkhatim; Imam, Sabrina; et al. (Cell reports (Cambridge), 2020)
The PD-1 pathway regulates dysfunctional T cells in chronic infection and cancer, but the role of this pathway during acute infection remains less clear. Here, we demonstrate that PD-1 signals are needed for optimal memory. Mice deficient in the PD-1 pathway exhibit impaired CD8+ T cell memory following acute influenza infection, including reduced virus-specific CD8+ T cell numbers and compromised recall responses. PD-1 blockade during priming leads to similar differences early post-infection but without the defect in memory formation, suggesting that timing and/or duration of PD-1 blockade could be tailored to modulate host responses. Our studies reveal a role for PD-1 as an integrator of CD8+ T cell signals that promotes CD8+ T cell memory formation and suggest PD-1 continues to fine-tune CD8+ T cells after they migrate into non-lymphoid tissues. These findings have important implications for PD-1-based immunotherapy, in which PD-1 inhibition may influence memory responses in patients. [Display omitted] •Early loss of PD-1 leads to overactivation of CD8+ T cells during acute infection•Mice constitutively lacking PD-1 or PD-L develop impaired CD8+ T cell memory•Cell-intrinsic PD-1 signals suppress effector cell expansion and promote memory•Timing of PD-1 blockade determines impact on memory generation The role of PD-1 in memory development is poorly understood. Here, Pauken et al. show that constitutive loss of PD-1 during acute infection causes overactivation of CD8+ T cells during the effector phase and impairs memory and recall responses. These data indicate PD-1 is required for optimal memory.